The Use of Immersive Environments for the Early Detection and Treatment of Neuropsychiatric Disorders - Martin, Robert F. K.; Leppink-Shands, Patrick; Tlachac, Matthew; DuBois, Megan; Conelea, Christine; Jacob, Suma; Morellas, Vassilios; Morris, Theodore; Papanikolopoulos, Nikolaos (Frontiers in Digital Health, 2021)
Neuropsychiatric disorders are highly prevalent conditions with significant individual, societal, and economic impacts. A major challenge in the diagnosis and treatment of these conditions is the lack of sensitive, reliable, objective, quantitative tools to inform diagnosis and measure symptom severity. Currently available assays rely on self-reports and clinician observations, leading to subjective analysis. As a step toward creating quantitative assays of neuropsychiatric symptoms, we propose an immersive environment to track behaviors relevant to neuropsychiatric symptomatology and to systematically study the effect of environmental contexts on certain behaviors. Moreover, the overarching theme leads to connected tele-psychiatry which can provide effective assessment.